PENERAPAN MEDIA PEMBELAJARAN MONOPOLI PANCASILA UNTUK MENINGKATKAN MOTIVASI BELAJAR PADA PEMBELAJARAN PENDIDIKAN PANCASILA SEKOLAH DASAR - Sofia Nur Amelia; Dian Permatasari Kusuma Dayu; Rosniwaty Rosniwaty; Himmatul Khoiroh; Kemas Abdussyukur (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to improve student learning outcomes in the Pancasila Education subject through the application of the Pancasila Monopoly learning media. This learning media was developed as an interactive and interesting tool for students, with the hope of increasing their motivation and understanding of Pancasila material. The research method used was classroom action research (PTK) which was carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection. The research subjects were class V students at SDN Gading V Surabaya, totaling 15 girls and 17 boys. The research results in cycle I were 62%, increasing to 31% in cycle II to 93%. Then the increase in learning motivation was shown by obtaining a percentage increase in students' learning motivation in the pre-cycle, which was originally 44%, increasing in cycle I by 18% to 62% and experiencing an increase of 31% in cycle II to 93%. Based on the research results, the application of the Pancasila Monopoly learning media in the Pancasila Education subject can increase the learning motivation of class V students at SDN Gading V Surabaya